2022
DOI: 10.3390/v14061123
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sphingosine Kinase Inhibitor Suppresses Chikungunya Virus Infection

Abstract: Chikungunya virus (CHIKV) is a re-emerging arbovirus in the alphavirus genus. Upon infection, it can cause severe joint pain that can last years in some patients, significantly affecting their quality of life. Currently, there are no vaccines or anti-viral therapies available against CHIKV. Its spread to the Americas from the eastern continents has substantially increased the count of the infected by millions. Thus, there is an urgent need to identify therapeutic targets for CHIKV treatment. A potential point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Recently, a promising vaccine candidate entered clinical trials (23), however, even with a viable vaccine there remain significant hurdles to effective prevention, containment, and control of any disease, especially in underdeveloped countries. There is a considerable amount of research devoted to the development of antivirals that may be useful as therapeutics for CHIKV disease (see 24 for review) including interferon (25), deubiquinating enzyme inhibitors (26), sphingosine kinase inhibitors (27), and radicol (28) and defective viral genomes (29).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a promising vaccine candidate entered clinical trials (23), however, even with a viable vaccine there remain significant hurdles to effective prevention, containment, and control of any disease, especially in underdeveloped countries. There is a considerable amount of research devoted to the development of antivirals that may be useful as therapeutics for CHIKV disease (see 24 for review) including interferon (25), deubiquinating enzyme inhibitors (26), sphingosine kinase inhibitors (27), and radicol (28) and defective viral genomes (29).…”
Section: Introductionmentioning
confidence: 99%
“…Kinase inhibitors, a largest and most functionally diverse gene family, are key regulators of cellular function and are associated with viral replication in influenza virus 16 , measles virus 17 , hepatitis C virus 18 , alphavirus 19 , dengue virus 20 , human immunodeficiency virus 21 , herpes simplex virus 22 and human papillomavirus 23 . Recent studies demonstrated that a sphingosine kinase inhibitor suppressed CHKV infection 19 , and Src family kinase inhibitors blocked the translation of alphavirus subgenomic mRNAs 24 . Some benzofurans were found to inhibit CHIKV-associated cell death in a dose-dependent manner by screening a kinase inhibitor library 25 .…”
Section: Introductionmentioning
confidence: 99%